2002
DOI: 10.1046/j.1365-2133.2002.04666.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in nickel sensitization in a Danish schoolgirl population with ears pierced after implementation of a nickel-exposure regulation

Abstract: As we found an effect of ear piercing before but not after 1992, this study strongly suggests that implementation of the nickel-exposure regulation in 1992 in Denmark has had the intended effect of protecting the female population from becoming allergic to nickel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
125
2
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(145 citation statements)
references
References 20 publications
12
125
2
6
Order By: Relevance
“…14,[16][17][18] Unfortunately, reports demonstrate that the EU directive is not always followed, [37][38][39] although violation of the nickel directive may lead to fines, detention, and even imprisonment. Nevertheless, it is foreseen that an effect from these directives could prevent nickel sensitization in millions of EU citizens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,[16][17][18] Unfortunately, reports demonstrate that the EU directive is not always followed, [37][38][39] although violation of the nickel directive may lead to fines, detention, and even imprisonment. Nevertheless, it is foreseen that an effect from these directives could prevent nickel sensitization in millions of EU citizens.…”
Section: Discussionmentioning
confidence: 99%
“…8 In 1990 and 1994, respectively, nickel directives were passed in Denmark and the European Union (EU) to diminish nickel release in consumer products. 12,13 The effect of these directives has so far been suggested in clinical [14][15][16] and populationbased 17,18 material. Because no such directive exists in the Unites States, we decided to purchase and examine costume earrings from a US city.…”
mentioning
confidence: 99%
“…A recent Danish study of schoolgirls suggested that implementation of the nickel-exposure regulation from the early 1990s protected females from becoming sensitized to nickel (23). This trend has not been seen in adults yet, but a falling rate of sensitization is expected in Europe (18).…”
Section: Discussionmentioning
confidence: 99%
“…Nikkelallergi er den vanligste form for kontaktallergi, og i EU ble salg av nikkelholdige produkter som vil vaere i kontakt med huden forbudt fra 1997. Man antar at dette tiltaket vil medføre at insidensen for nikkelallergi avtar (12). Flere studier viser at insidensen av kontaktallergi er høyere hos kvinner enn hos menn (7).…”
Section: Kontaktallergiunclassified
“…Kontaktallergi kan utredes med epikutantester (lappetest, patchtest) (6,8,9,(12)(13)(14). Man har et antall testserier.…”
Section: Utredning Av Kontaktallergiunclassified